Clinical Outcomes of Children With Prenatal Hydronephrosis: Prenatal Hydronephrosis - Ghadery, Milad; Bazargni, Behnaz; Abbasi, Arash; Moghtaderi, Mastaneh (Journal of Pediatric Nephrology, 2022)
Background: Fetal hydronephrosis (HY) is a frequent congenital condition that may be detected by prenatal ultrasound studies. The main underlying abnormalities found in these cases after birth are ureteropelvic junction stenosis, primary vesicoureteral reflux, megaureter, duplex kidneys, and posterior urethral valves, with uretero-pelvic junction stenosis and primary vesicoureteral reflux accounting for most cases. Method: Neonates with a prenatal diagnosis of congenital HY born between 2017 and 2020 were referred to our center for the appropriate management and follow-up and were included in this cross-sectional study. Ultrasonographic studies were performed in all these neonates in the first week of birth. Prenatal HY was categorized as mild, moderate, severe, and highly severe when the antero-posterior diameter of the renal pelvis was less than 5 mm, between 5 mm and 10 mm, between 10 mm and 15 mm, and more than 15 mm, respectively. Results: A total of 164 children with prenatal HY were included in this study. 84 patients (51.2%) had unilateral HY and 80 patients (48.8%) had bilateral HY. Twelve patients had posterior ureteral valves and 64 patients (39%) had vesical-urethral reflux (VUR). no significant relationship was observed between unilateral or bilateral reflux and outcome (P value 0.645). Conclusion: Prenatal screening of HY is vit